Pengaruh Positive Reinforcement terhadap Minat Belajar pada Lansia dalam Kegiatan Bimbingan Psikososial di Panti Sosial Tresna Werdha Budi Mulia 3 - Salwa Nadhira Burhani; Vidya Dela Prita; Salsabila Aprila; Thesa Risanda Putri; Muhammad Rizki Azhari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The growing elderly population in Indonesia highlights the need for effective psychosocial interventions that can enhance learning interest and active participation among older adults living in social care institutions. One approach that has potential but remains underexplored in this context is positive reinforcement. This study aimed to examine the effect of positive reinforcement on the learning interest of elderly individuals participating in psychosocial guidance activities at the Tresna Werdha Budi Mulia 3 Social Welfare Institution, Jakarta. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design. A total of 30 elderly participants were divided equally into an experimental group, which received positive reinforcement, and a control group, which received no reinforcement. Learning interest was measured using an instrument developed based on B. F. Skinner’s operant conditioning theory. Data analysis was conducted using Jamovi software, including normality testing and t-test analysis. The results indicated that the data were normally distributed. Statistical analysis revealed a significant difference in posttest learning interest scores between the experimental and control groups (p < 0.001). The experimental group demonstrated substantially higher learning interest compared to the control group, with a very large effect size, indicating a strong practical impact. These findings suggest that positive reinforcement is an effective strategy for enhancing learning interest among older adults in psychosocial guidance settings.